Penggunaan Theoretical Framework of Acceptability untuk Menilai Program Pencegahan Kehamilan Remaja: Dalam Konteks Penaggulangan Stunting di DI Yogyakarta. Using the Theoretical Framework of Acceptability for assessment of the preventing teen pregnancy program: In the context of stunting reduction in Yogyakarta - Tri Siswati; Eni Maryuni; Lutfi Rahmawati; Rahmad Satya Nugroho; Muhammad Primiaji Rialihanto; Yustiana Olfah (Jurnal Kebijakan Kesehatan Indonesia, 2022)
Pregnancies that occur at a younger age should be avoided because they are the root cause of childhood growth retardation. This study aims to assess the innovation of early pregnancy prevention programs (namely Emping Jamil or in Bahasa, Pendampingan Remaja untuk Ibu Hamil)) using the Theoretical Framework of Acceptability (TFA). This research is a mixed-method with quantitative data for assessing program indicator achievements, early pregnancy incidence, and stunting prevalence. Meanwhile, qualitative research was carried out with a rapid assessment procedure (RAP) design. The research was conducted in Terong Village, Dlingo II Health Center, Bantul Regency, Yogyakarta in July-August 2022. Quantitative data is analyzed by trend, and qualitative data is analyzed by theme. As a result, the Dlingo II Health Center implemented a program for preventing early pregnancy Emping Jamil since 2016. During 2016–2021, all program indicators increased, while the rate of early pregnancy and stunting prevalence decreased. The results of the TFA analysis stated that the Emping Jamil program is very linear with the government's efforts to overcome stunting through early pregnancy prevention (ethics), increasing knowledge, understanding, and public perception of the health of pregnant women and toddlers (perception of effectiveness), and all components of society understand how to have a positive attitude towards interventions (positive affective attitudes), play an active role and support the program (koherence), and increasing of pregnant women well-being, adolescent understanding of pregnancy, delaying the age of marriage, and reducing the prevalence of stunting (effectiveness of the intervention). The program is supported by financing derived from waste banks, community funds, and Puskesmas and is carried out by trained adolescent assistance personnel (burden). In conclusion, the Emping Jamil program can be accepted by all communities so that it succeeds in eliminating early pregnancy, improving the welfare of pregnant women, and reducing the stunting prevalence.